Effects of the ethyl acetate fraction of Alchornea triplinervia on healing gastric ulcer in rats - Lima, Zeila P. [UNESP]; Bonamin, Flavia [UNESP]; Calvo, Tamara R. [UNESP]; Vilegas, Wagner [UNESP]; Santos, Lourdes C. [UNESP]; Rozza, Ariane L. [UNESP]; Pellizzon, Claudia H. [UNESP]; Rocha, Lucia R. M. [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (MDPI, 2011)
Alchornea triplinervia (Spreng.) Muell. Arg (Euphorbiaceae) is a medicinal plant commonly used by people living in the Cerrado region of Brazil to treat gastrointestinal ulcers. We previously described the gastroprotective action of methanolic extract (ME) of Alchornea triplinervia and the ethyl acetate fraction (EAF) in increasing of prostaglandin E 2 (PGE 2) gastric levels in the mucosa. In this work we evaluated the effect of EAF in promoting the healing process in rats with acetic acid-induced gastric ulcers. In addition, toxicity was investigated during treatment with EAF. After 14 days of treatment with EAF, the potent stimulator of gastric cell proliferation contributed to the acceleration of gastric ulcer healing. Upon immunohistochemical analysis, we observed a pronounced expression of COX-2, mainly in the submucosal layer. The 14-day EAF treatment also significantly increased the number of neutrophils in the gastric mucosa regeneration area. The EAF induced angiogenesis on gastric mucosa, observed as an increase of the number of blood vessels supplying the stomach in rats treated with EAF. Oral administration for 14 days of the ethyl acetate fraction from Alchornea triplinervia accelerated the healing of gastric ulcers in rats by promoting epithelial cell proliferation, increasing the number of neutrophils and stimulation of mucus production. This fraction, which contained mainly phenolic compounds, contributed to gastric mucosa healing. © 2011 by the authors; licensee MDPI, Basel, Switzerland.
Keywords: Alchornea triplinervia; Angiogenesis; Euphorbiaceae; Healing ulcer effect; Phenolic compounds; acetic acid ethyl ester; Alchornea triplinervia extract; antiulcer agent; cimetidine; cyclooxygenase 2; plant extract; unclassified drug; angiogenesis; animal cell; animal experiment; animal model; animal tissue; cell proliferation; controlled study; dose response; drug effect; drug mechanism; drug screening; Euphorbia; immunohistochemistry; male; mucus secretion; neutrophil count; nonhuman; plant leaf; protein expression; rat; single drug dose; stomach mucosa injury; stomach protection; stomach ulcer; tissue regeneration; toxicity testing; ulcer healing; ulcerogenesis